Conceptualising 'Learning' in Applied Linguistics
XIV, 291 p.
Keywords: An exciting new collection by world-leading researchers in L2 learning addressing: Why do conceptions of 'learning' vary so much in L2 learning research? Is there a conceptualisation of 'learning' to which members of different schools of SLA can subscribe?